Influence of Antioxidants and Salinity Stress on Seed Viability Characters of Some Wheat Cultivars - A. E. Sharief, A. A. Kandil,; Botabaah, Alkhamsa K. D. (Research in Plant Biology)
To explore the impact of antioxidants types and levels prim on seed germination characters of some bread wheat cultivars under salinity stress. An experiment accompanied in seed science lab during November and December 2016, to study the response of antioxidants seed prim of some bread wheat cultivars to germinate under salinity levels. The highest of final percentages of germination (96.8 %), higher percentages of germination energy (58.11 %), highest values of germination index (0.970) and a smaller amount of germination time (2.29 day) obtained from sown Misr 1 variety. The results showed that maximum of percentages of germination (91.15 %) and germination index (0.951) obtained from soaking in humic acid. The maximum percentages of energy of germination (41.21 %) and the less mean germination time (2.77 day from soaking grains in ascorbic acid compared with without antioxidants. Increasing antioxidant concentrations to 200 ppm produced the highest percentages of germination (91.61 %), energy of germination (37.63 %), germination index (0.953) and the lowermost of mean germination time (2.97 day) compared with without antioxidants and level of 100 ppm. Increasing salinity to 160 mM during germination of wheat cultivars significantly reduced percentages of germination by 18.5 %, energy of germination by 96.7 %, germination index by 18.6 % and mean germination time by 53.5 % compared with without salinity (control). Whereas, for reducing the gap between production and consumption, it could be recommended that soaking bread wheat in humic acid or ascorbic acid at 200 mM under salinity stress enhanced seed viability and advise to sown under saline new reclaimed soil.